Premios Instituto Henry Moore. - Museo Nacional de Bellas Artes, Buenos Aires; Faccaro, Rosa; Gercovich, Felipe Gustavo; Glusberg, Jorge (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1998)
Aranovich, Claudia ; Correas, Nora ; Danziger, Danilo ; Daz, Alberto Bastón ; Dompé, Hernán ; Garnarra, Jorge ; Gómez, Fabriciano ; Gómez, Pájaro ; Madanes, Edgardo ; Nardi, Rudolfo ; Pacenza, Lucia ; Schapiro, Mariana
biografie
Premios Instituto Henry Moore, MNBA - Museo Nacional de Bellas Artes Buenos Aires, diciembre 1998
Spaans
boek